Teacher Competency Development Through On-The-Job Training: A Case Study at SDIT Lan Tabur Purwodadi - Istiqomah, Devi; Purwanto, Nurtanio Agus (Green Publisher Indonesia, 2023)
On-the-job training is practical if it suits the needs of the teacher. However, there still needs to be more competence and training in schools. This study aims to analyze teacher competency development through on-the-job training. This research uses a qualitative approach in the form of a case study at SDIT Lan Tabur Purwodadi. The data collection method uses observation, interviews, and documentation. The subjects in this study were principals and teachers. Data analysis techniques with data collection, data reduction, data presentation, conclusion, and data verification. The results showed that through on-the-job training, teacher competence could develop well, teacher pedagogic competence develops in managing learning in the classroom, and teacher social competence is also well developed and can provide a foundation for social problems in schools. Teacher personality competence develops with on-the-job training, but it is different from the professional competence of teachers, which is less developed due to the lack of teachers conducting research and the use of technology, which still needs to be improved. This is because the facilities and infrastructure at SDIT Lan Tabur Purwodadi need to be improved. Through on-the-job training, teacher competence becomes very developed. The implications of this research are expected through on-the-job training to develop teacher competence and provide solutions to teacher competence problems in schools.